The applicability of the P-Star approach of modelling inflation in a developing country : The case of Malaysia - Habibullah, Muzafar Shah (Universiti Utara Malaysia, 1998)
The P-Star approach of modelling inflation proposed by Hallman et al. (1989) has been widely tested for the United States and other developed countries. However, the applicability of the P-Star model for the developing countries is yet to be determined. Thus, the main purpose of the present paper is to add to the current literature on the robustness of the P-Star approach by testing in with respect to a developing country-malaysia. Using a sample period of 1981:1 to 1991:4, our results suggest that the monetary data for Malaysia do not support the P-Star model approach of modelling inflation.